Anxiety Disorders in the Workplace: How to Deal and Does Anxiety Affect Employee’s - Fadillah Ismail,; Adnan Ali Alhossani, (Journal of Techno-Social, 2024)
In recent years, mental health disorders are a huge public health problem worldwide, especially anxiety disorders. Anxiety disorders is the extreme worry or fear under the category of psychiatric conditions. To gain a better understanding of the topic of anxiety disorders in the workplace, the researcher conducted a literature review of previous articles to support the objectives of the study. The objectives of the study are to determine the factors of anxiety disorders among employees in the workplace, to determine the ways to manage anxiety disorders for employees, and to examine the impact of anxiety disorders on employee’s abilities. This study elaborated 6 ways for employees to overcome their anxiety disorders in the workplace, such as awareness, having a conversation between employers and employees, supportive family and friends, practicing a healthy lifestyle, mindfulness practicing, and setting deadlines honestly. Moreover, anxiety disorders have reduced of anxiety disorders on the employee’s abilities are reduced productivity, employee planning less effectively, less focus on work and have difficulty in listening. Additionally, this study made several recommendations on how employers assist their employees who experience anxiety disorders. Overall, the future researcher needs to be explored the psychological well-being of employees in the workplace in the future in order to stay in a peaceful and harmonious working environment.